If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 3 + -7x = 83 Reorder the terms: 3 + -3x + -7x = 83 Combine like terms: -3x + -7x = -10x 3 + -10x = 83 Solving 3 + -10x = 83 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -10x = 83 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = 83 + -3 -10x = 83 + -3 Combine like terms: 83 + -3 = 80 -10x = 80 Divide each side by '-10'. x = -8 Simplifying x = -8
| 6-5x-2=4x-2-1 | | 6-5x-2=4x-2-11 | | 12+3x-7x=x+7 | | 6-5x=4x-1 | | y=3.43*200+4 | | -6m-2m=10 | | 4(7-2y)+3y=3 | | 7+33X-16x^2=23 | | 91.17=.11x+3.17 | | 23.08=1x+3.08 | | -2+7x-6x=4 | | 5x+2x-18=77+3 | | 3y=3y+1 | | ln(y)=5 | | 2+4(2z+3)=15 | | 2y*y*7=56 | | 7(-8+2m)-3m= | | 78=6x+6x-6 | | ln(x-2)+5=7 | | 15x-3(3x-2)=45-5(2x-5) | | 5(-6f-9)= | | .5k+2=5+8.3k | | 2(12-x)=-76-x | | -6k-8(3+7k)= | | 60=-2x+7x+5 | | 6(-2w-4)= | | log(x+12)+log(X-3)=2 | | -8(-7-3r)= | | -4(5-6d)+2= | | 2x+(-4x)-x=0 | | 23=7x+6x+10 | | -7-2(9-4g)= |